A Periodic Event-Triggered Vehicle Platooning Scheme Against Denial-of-Service Attacks - Liu, Jingxuan; Ding, Sanbo; Jing, Yanhui; Xie, Xiangpeng (IEEE transactions on intelligent vehicles, 2024)
This paper is concerned with a periodic event-triggered control problem of vehicle platooning systems over vehicular ad-hoc networks (VANETs) subject to denial-of-service (DoS) attacks. First, in order to save limited bandwidth resources, a periodic event-triggered communication mechanism is developed under DoS attacks which interrupt the control signal transmission intermittently. Compared with common event-triggered mechanisms (ETMs), it enables monitoring periodically and increases effectively the lower bound of event intervals. Second, in order to evaluate the impact of DoS attacks and periodic ETM on the platoon, a switched system model is established which combines periodic sampling and DoS attacks scenarios uniformly. Furthermore, by using a novel piecewise Lyapunov functional, the co-design criterion is obtained for event-triggered parameters and resilient platooning controller. Such functional not only matches the sawtooth constraint but also accommodates the adverse impacts of DoS attacks. Finally, adequate numerical experiments are supplied to verify the superiority of the theoretical results.